1994
DOI: 10.1111/j.1472-765x.1994.tb00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three rapid methods for identification of Salmonella spp

Abstract: A study was carried out to compare three rapid methods for detection of Salmonella spp. The fluorogenic MUCAP test (Biolife, Italy), the SM‐ID agar test (bioMérieux, France) and the Rambach agar test (Merck, Germany) were used in this study to examine 103 strains (69 Salmonella strains and 34 non‐Salmonella strains). Two conventional culture media, Hektoen and Leifson agars, were also included. The sensitivities of the MUCAP, SM‐ID, Rambach and Hektoen agar tests for pure strains were 100, 93, 88 and 99%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…which are capable of fermenting that sugar (2). Several investigators have already pointed out the lack of selectivity of SM in direct sampling (5,6,8,9). In our study, although we used a new formula proposed by the manufacturer, the selectivity did not improve appreciably, overlooking in many cases the isolation of salmonellae.…”
Section: Discussionmentioning
confidence: 64%
“…which are capable of fermenting that sugar (2). Several investigators have already pointed out the lack of selectivity of SM in direct sampling (5,6,8,9). In our study, although we used a new formula proposed by the manufacturer, the selectivity did not improve appreciably, overlooking in many cases the isolation of salmonellae.…”
Section: Discussionmentioning
confidence: 64%
“…Rambach agar (E. Merck, Darmstadt, Germany) and SM-ID medium (bioMerieux S.A., Montalieu-Vercieu, France) have recently been introduced as new selective media for the isolation of salmonellae. Several investigators have already reported high rates of sensitivity and specificity for Rambach agar (1, 4, 5, 7) and SM-ID medium (8), but their investigations were essentially based on the use of pure Salmonella stock cultures (4,5,7) or they tried to isolate Salmonella spp. from marine waters (1).…”
mentioning
confidence: 99%
“…also fluoresced (6). Thus, although the sensitivity of the MUCAP test was high (100%), the specificity was low (80%), especially compared to that of a latex slide agglutination test (96%) (9).…”
mentioning
confidence: 94%